Basic characteristics of offensive modalities in the Euroleague and the NBA - Selmanovic, A.; Skegro, D.; Milanovic, D. (Acta Kinesiologica, 2015)
This paper presents fundamental structural features of basketball offense in professional basketball. Offensive categories were classified on strict operational definitions and evaluated according to their type, duration, a method of its beginning and finishing action. The analysis was done separately for Euroleague and the NBA offensive models. Using a sample of 5718 entities, the results showed many similarities between the European and American basketball among which should be emphasized the equal pace and dynamics of the game. The differences between the two analyzed models can be seen in unbalanced distribution of basic types of offenses, their particular beginning and tactical variants of their finish.